Franciszka Ksawerego Bohusza uwagi o prawie sądowym w podróżach po Europie poczynione - Mikołajczyk, Marian (Z Dziejów Prawa [czasopismo zamknięte], 2020)
Franciszek Ksawery Bohusz (1746—1820), Jesuit and diocese priest after the dissolu- tion of the monastery, was a man educated in philosophy, theology, and law. Between 1777—1778 and 1781—1782, he made long journeys abroad, during which he got to know Czechia, Germany, France, England, Austria, Italy, and Switzerland. These were the journeys of an intellectual, typical of the period of Enlightenment. Not only did he admire edifices worthy of interest, visit museums and libraries, but he also tried to gain knowledge of the political regimes, social and economic relations in the visited countries. His observations were diligently noted down in travel journals and finally edited upon his return to the country. A lot of comments concern court law: civil and criminal, particularly procedural law. The traveler was also interested in the administra- tion of punishments. The references to law vary from extensive, comprehensive discussions of whole branches of law to prevailing brief mentions of particularly interesting legal institutions. The author attempts to offer a possible objective view of legal solutions he became familiar with, yet, does not always fully succeed. It is worth noting his commentaries on English law, which are not only exception- ally extensive, but also filled with not always well-justified praise. On the other hand, his evalua- tions of other legal systems, for instance Swiss, seem to be rather harsh and stereotypical. Nevertheless, Franciszek Ksawery Bohusz’s observations on court law in the visited coun- tries deserve a thorough analysis since they let us assess their accuracy and the degree to which some foreign legal solutions found appreciation in his eyes.